THE RELATIONSHIP OF BODY MASS INDEX (BMI) AND INCREASING BLOOD GLUCOSE LEVELS DURING STUDENTS IN THE FACULTY OF MEDICAL EDUCATION PROGRAM, ABULYATAMA UNIVERSITY - Sulviani Fitri; Farid Bastian; Elmiyati (PT. Radja Intercontinental Publishing, 2024)
Body weight is one of the parameters that provides an idea of ​​body mass. Normal or ideal body weight is if height and weight are balanced. The normal weight limit for adults is determined based on the body mass index (BMI) value. According to WHO 2024, there are around 2 billion adults who are overweight and 650 million people who are obese, with an estimated increase to 2.7 billion in 2025. Diabetes mellitus is a metabolic disorder characterized by high levels of glucose in the blood caused by a insulin production, insulin resistance, and suboptimal insulin action. Indonesia is the 7th highest with the number of diabetes sufferers reaching 10 million people and is predicted to increase to 16.2 million people in 2040. This research aims to prevent diabetes mellitus which is influenced by obesity in students of the Medical Education Study Program, Faculty of Medicine, Abulyatama University, by focuses on temporary increases in blood glucose levels and the risk of metabolic disease due to abnormal blood glucose control and BMI. This research is an analytical observational study with a cross sectional approach, where researchers collected primary data obtained from the results of examinations of body mass index (BMI) and blood glucose levels at Abulyatama University, Faculty of Medicine, Medical Education Study Program, class of 2020, class of 2021, class of 2022, and class of 2023. The results of this study show a significant relationship between BMI and an increase in blood glucose levels at any time (p-value = 0.000). As many as 52% of students had blood glucose levels <140 mg/dL, 37.3% had blood glucose levels of 140-199 mg/dL, and 10.7% >200 mg/dL. Based on BMI, 38.7% of students are normal, 25.3% are obese 1, 14.7% are obese 2, 13.3% are overweight, and 8% are underweight.